2017
DOI: 10.1007/s00526-017-1123-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimal graphs in $$Nil_3:$$ N i l 3 : existence and non-existence results

Abstract: We study the minimal surface equation in the Heisenberg space, N il3. A geometric proof of non existence of minimal graphs over non convex, bounded and unbounded domains is achieved (our proof holds in the Euclidean space as well). We solve the Dirichlet problem for the minimal surface equation over bounded and unbounded convex domains, taking bounded, piecewise continuous boundary value. We are able to construct a Scherk type minimal surface and we use it as a barrier to construct non trivial minimal graphs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Fernández and Mira [14] showed that there exists a vast family of entire minimal graphs in Nil 3 (τ ), namely, they can associate to each holomorphic quadratic differential Q on C or D = {z ∈ C : |z| < 1} a 2-parameter family of entire minimal graphs with Abresch-Rosenberg differential Q. The only restriction is Q = 0 if the domain is C. [26] proved that, for any wedge S with vertex at the origin and angle θ ∈] π 2 , π[, there exists a non-zero minimal graph over S, with zero boundary value. Here the proof is based on classical PDE's theory joint with a suitable construction of barriers.…”
Section: Minimal Graph Equation In E(κ τ ) and Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernández and Mira [14] showed that there exists a vast family of entire minimal graphs in Nil 3 (τ ), namely, they can associate to each holomorphic quadratic differential Q on C or D = {z ∈ C : |z| < 1} a 2-parameter family of entire minimal graphs with Abresch-Rosenberg differential Q. The only restriction is Q = 0 if the domain is C. [26] proved that, for any wedge S with vertex at the origin and angle θ ∈] π 2 , π[, there exists a non-zero minimal graph over S, with zero boundary value. Here the proof is based on classical PDE's theory joint with a suitable construction of barriers.…”
Section: Minimal Graph Equation In E(κ τ ) and Examplesmentioning
confidence: 99%
“…This result is sharp, as half of a catenoid or planes of the form u(x, y) = ax + by show. Other non-trivial examples of graphs over a sector with angle between π 2 and π, with either linear or at least quadratic height growth, are given in [3] and [26] (see also Section 3).…”
Section: Corollarymentioning
confidence: 99%
See 1 more Smart Citation
“…At last, the general a priori gradient estimates carry out by H. Rosenberg, E. Toubiana and R. Souam [, Theorem 3.6] has been applied to solve Dirichlet problems in homogeneous spaces .…”
Section: Uniform Global Gradient Estimatesmentioning
confidence: 99%
“…Although this was already known, see [2,8,16], our approach also shows that invariant examples are related by hyperbolic deformations. Some other invariant examples will be discussed throughout the paper, though very few examples of explicit entire minimal graphs are known so far (e.g., the examples constructed by Cartier [5] or Nelli, Sa Earp and Toubiana [30] fail to be explicit).…”
Section: Introductionmentioning
confidence: 99%